Evaluasi Hasil Kesamaptaan Jasmani Terhadap Kinerja Anggota Polri Mapolda Jawa Tengah - Sari, Dyah Puspita; Hanani, Endang Sri; Priyono, Bambang (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to examine and analyze the level of physical fitness of members of the Central Java Regional Police Headquarters who are in charge of staff and operations in the 12-minute running, pull-up or chinning, sit-up, push, and shuttle run test components. This research uses a qualitative approach method. Data collection techniques include interviews, observation, and documentation. The data analysis stage uses qualitative analysis, including data collection, reduction, delivery, and conclusions. The results of the research show the level of physical fitness of members of the National Police at the Central Java Regional Police Headquarters who served in staff and operations for the period 2019 to 2019. 2023 received an overall score of 53.88 in the Fair (C) category; 2 (two) factors influence the level of physical fitness, namely internal and external factors. There is a relationship between physical fitness and performance level. Conclusion: The level of physical fitness of members of the National Police at the Central Java Regional Police Headquarters who served in staff and operations from 2019 to 2019. 2023 received an overall score of 53.88 in the Fair (C) category. Key words: physical fitness, National Police, performance